2018
DOI: 10.1016/j.ajme.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Results of arthroscopic treatment of femroacetabular impingement (FAI)

Abstract: Introduction: Femoroacetabular impingement (FAI) has been suggested as an important etiology of pain in the groin region in young adults especially athletes and there are theories connecting it to early onset osteoarthritis. Aim: To assess the results of arthroscopic treatment of FAI. Patients: Forty patients had been managed arthroscopically for their FAI in both El-Hadra university hospital and William Harvey Hospital. Methods: Results of arthroscopic treatment of FAI in 40 consecutive patients had been eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Postoperative changes in flexion from each study’s baseline were reported as statistically significant in 57.1% (12/21), not statistically significant in 14.3% (3/21), and statistical significance was not reported in 28.6% (6/21). For those studies reporting statistically significant change in flexion, effect size was weak in 16.7% (2/12) 35 , 36 of studies, moderate in 58.3% (7/123), 27 , 29 , 37 , 38 , 39 , 43 , 45 and large in 25% (3/12) 32 , 34 , 46 of studies. Pre- to postoperative measured changes in flexion for studies evaluating unilaterally operated patients are presented in Figure 2 A, whereas those studies evaluating a mix of unilateral and bilateral patients are presented in Figure 3 A.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Postoperative changes in flexion from each study’s baseline were reported as statistically significant in 57.1% (12/21), not statistically significant in 14.3% (3/21), and statistical significance was not reported in 28.6% (6/21). For those studies reporting statistically significant change in flexion, effect size was weak in 16.7% (2/12) 35 , 36 of studies, moderate in 58.3% (7/123), 27 , 29 , 37 , 38 , 39 , 43 , 45 and large in 25% (3/12) 32 , 34 , 46 of studies. Pre- to postoperative measured changes in flexion for studies evaluating unilaterally operated patients are presented in Figure 2 A, whereas those studies evaluating a mix of unilateral and bilateral patients are presented in Figure 3 A.…”
Section: Resultsmentioning
confidence: 95%
“…Postoperative changes in IR from each study’s baseline were statistically significant in 74% (17/23), whereas statistical significance was not reported in 26% (6/23). For those studies reporting statistically significant improvements in IR, effect size was moderate in 29.4% (5/17) 27 , 28 , 35 , 36 , 38 of studies, and large in 64.7% (11/17) 30 , 32 , 33 , 34 , 37 , 39 , 43 , 44 , 45 , 46 , 48 of studies. One further study (1/17), 29 evaluating 2 groups of patients, reported a moderate effect size in patients without generalized joint laxity and a large effect size in those with generalized joint laxity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation